Transforming Character Education in Balancing Citizens' Rights and Obligations for Social Harmony - Yogi Yulihastoro Wahyudi; Afif Raihan Raditya (Aslim: Journal of Education and Islamic Studies, 2026)
The rights and obligations of citizens are two fundamental concepts that form the foundation of national and state life. In the Indonesian context, these two aspects are not only rooted in formal legal norms such as the 1945 Constitution, but also based on the values ​​of Pancasila, which regulate how citizens should behave in social life. This study aims to analyze the reciprocal relationship between the rights and obligations of citizens, explain the urgency of harmonizing them, and identify the main obstacles that hinder their implementation in modern society. This study uses a literature review method by analyzing five academic journals that discuss issues surrounding citizenship, democracy, Pancasila, and the implementation of rights and obligations in Indonesia. The results of the study indicate that the imbalance between rights and obligations results in social tensions, low legal awareness, and a decline in the quality of democracy. Furthermore, it was found that factors such as unequal fulfillment of rights, low civic literacy, weak character education, and inconsistent law enforcement contribute to exacerbating social disharmony. This study concludes that to achieve a harmonious social life, collaboration between the government and citizens is necessary through civic empowerment, equal access to basic rights, and increased awareness of obligations through education and consistent law enforcement.